ICCREM 2022 proceedings of the International Conference on Construction and Real Estate Management 2022, December 17-18, 2022 - Wang, Yaoyu; Lin, Shaohua (Civil engineer); Shen, Qiping (American Society of Civil Engineers, 2022)
This collection contains 95 peer-reviewed papers highlighting carbon emissions and environmental impacts of the construction industry presented at the International Conference on Construction and Real Estate Management 2022, held virtually December 17-18, 2022. Topics include: low carbon construction and building; innovative technology and intelligent construction; real estate and urban management; and construction enterprises and project management.